STUDI PADA PESERTA DIDIK HOMOSEKSUAL DI SMA KOTA PONTIANAK - Theresia Clara; Yuline; Halida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The presence of homosexual students presents unique challenges in school guidance and counseling services. This study aims to describe the characteristics, causal factors, behavioral impacts, and the role of guidance and counseling teachers in assisting homosexual students at a senior high school in Pontianak City. Using a qualitative approach with a descriptive case study method, the research involved two homosexual students and four additional participants (BK teacher, homeroom teacher, and peers). Data were collected through interviews, observation, and documentation, and analyzed using data reduction, presentation, and conclusion drawing. Findings show that the subjects displayed gender non-conforming behaviors, identity conflicts, and selective social interactions. The causes were mainly psychological and social such as absence of a father figure, childhood trauma, and media influence. The impacts included psychological stress and limited interaction, though academic performance remained stable. BK teachers played a key role through individual counseling and by fostering an inclusive school environment.